Islamic Ornaments Center Di Demak - JAMALUDDIN, RIZQI, Dr. Ir. Dhani Mutiari, MT (2016)
Ornaments Islamic Center is a regional craft Islam as well as tourist and educational activities in which there are a manufacture, and education to learn Ornaments Islam. In addition there are supporting activities that visitors interact and produce her artwork senidiri in the form of goods. Visitors will be presented with the atmosphere of the Middle East region as a characteristic that would get the feeling that is really different when you're in this place. Demak is districts in Central Java. Demak has Demak Great Mosque as a landmark Islamic. On demak lot of Islamic boarding school and a place that teaches a wide range of religious activities. Islamic community here that has a lot of talent in the field of Islam. Demak itself is an area that has a high value so that the potential of Islam as a religious tourism as well as the place of production. The concept design of this educational area should be in harmony with the exterior and interior design to create an atmosphere of comfort for the occupants and visitors and people living environment. Thus the integrity in this area will remain intact and provide benefits to the general public Keywords: Islamic Garden, Islamic Ornaments Center, Building Islamic Center in Demak